2016
DOI: 10.1111/inm.12265
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of pro re nata medication use at a Canadian psychiatric hospital

Abstract: Pro re nata (PRN), a Latin phrase meaning 'as needed', is used to describe medications that might be used in specific situations, in addition to regularly-scheduled medications, such as when a patient is particularly anxious, experiencing insomnia, or suffering pain. While helpful in some circumstances, PRN are associated with an increased risk of morbidity, overuse, dependence, and polypharmacy. There is also a dearth of medical literature describing current practices and trends of PRN administration in menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 13 publications
1
64
0
Order By: Relevance
“…effectiveness, side‐effects) of PRN medication use on all inpatient units at our hospital, readers are directed to our previous publication (see Martin et al . ). In general, our snapshot revealed that 91% of inpatients received at least one PRN, there was a small group of patients who received the majority of the PRN medications (15% of patients received 70% of the medication), and benzodiazepines made up the majority of the PRN administered (52%).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…effectiveness, side‐effects) of PRN medication use on all inpatient units at our hospital, readers are directed to our previous publication (see Martin et al . ). In general, our snapshot revealed that 91% of inpatients received at least one PRN, there was a small group of patients who received the majority of the PRN medications (15% of patients received 70% of the medication), and benzodiazepines made up the majority of the PRN administered (52%).…”
Section: Resultsmentioning
confidence: 97%
“…The present study is a quantitative design with a retrospective chart review that was approved by our local research ethics board and was part of a larger study, a portion of which, including the methodology, was previously published in this journal (Martin et al . ). Briefly, we initially identified all psychotropic PRN administrations between 1 June 2015 and 31 August 2015 across all inpatient units.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Martin et al . ). The most common indications for this medication are agitation, anxiety, and insomnia (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…; Martin et al . ; Srivastava ). Other reasons psychotropic PRN medications are administered include verbal aggression, irritableness, intrusiveness, refusal to cooperate, refusal of scheduled medication, restlessness, and as requested by the patient (e.g.…”
Section: Introductionmentioning
confidence: 99%